The Effects of Merger and Acquisitions on Acquiring Firms’ Leverage Levels: Evidence from Indonesia - Nadia Aqmarina , Dony Abdul Chalid (International Journal of Advanced Science and Technology, 2020)
This study investigates whether firms in an emerging country have leverage targets andperform leverage adjustments. Using data from the Indonesian market, this study is to find out iffirms conducting merger and acquisitions (M&As) have targeted levels of leverage and willattempt to make adjustments of the leverage ratios to the projected optimum levels. The sampleincludes financial data between 2000 and 2019. The results show that acquiring firms havetargeted levels of leverage, and M&A events trigger the changes in the leverage ratios of thefirms. However, the acquiring firms do not constantly make adjustments of their leverage ratiosto the projected optimum levels in the post-announcement period. These firms also demonstraterelatively slower adjustment speeds compared to the previous studies. Hence the results of thisstudy indicate that Indonesian acquirers do neither fully follow the notions under the trade-offtheory nor the pecking order theory in organizing their capital structure.